1993
DOI: 10.1159/000292632
|View full text |Cite
|
Sign up to set email alerts
|

A New Technique for Improved Diagnosis of Local Placental Abnormalities: Fourier Analysis of Intraplacental Waveforms

Abstract: A new method to diagnose localized placental lesions is introduced. The method involves Fourier analysis of intraplacental and umbilical Doppler velocity waveforms. It is shown, using a theoretical model based on an electrical transmission line approach, that intraplacental waveforms that are of higher pulsatilities than those in the umbilical artery indicate placental abnormalities. The method was applied in a series of cases with normal umbilical waveforms in which placental abnormalities were diagnosed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…In our previous work [29] we were able to show theo retically that there is a downstream pulsatility gradient within the vascular tree of the normal placenta as also observed and hypothesized by Jauniax et al [30] and Hsic et al [31], Our model proved theoretically that local intra placental vascular disorders, which may have a negligible effect on the UA Doppler waveforms, could be detected based on the placental arterial downstream pulsatility gra dient. The theory has also been supported by some clini cal data.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…In our previous work [29] we were able to show theo retically that there is a downstream pulsatility gradient within the vascular tree of the normal placenta as also observed and hypothesized by Jauniax et al [30] and Hsic et al [31], Our model proved theoretically that local intra placental vascular disorders, which may have a negligible effect on the UA Doppler waveforms, could be detected based on the placental arterial downstream pulsatility gra dient. The theory has also been supported by some clini cal data.…”
supporting
confidence: 84%
“…Based on our proposed theoretical model [29], a new Doppler method for the early diagnosis of placental disorders, in terms of the described classification scheme is proposed. The method is based on a mathematical analysis of the UA waveforms as well as the intraplacental downstream pul satility gradient.…”
mentioning
confidence: 99%
“…The advantage of a detailed analysis of intraplacental Doppler waves is that it may identify fetoplacental circulation abnormalities earlier in gestation before these changes elicit an effect on the UA Doppler indices. Preliminary studies on the assessment of the intraplacental Doppler pulsatile indices (PI) during the second and third trimesters have been encouraging [15][16][17]. We have previously shown that the new Doppler method is reliable and can be used for the assessment of the fetoplacental circulation [1].The efficacy of this method in the prediction of adverse pregnancy outcome related to placental pathology has been described previously [17][18][19].…”
Section: Introductionmentioning
confidence: 93%
“…The major decrease in the arterial pressure across the umbilicoplacental circulation occurs in the small arteries and arterioles, the resistance vessels, of the tertiary stem villi, leading to the UA-intraplacental resistance gradient. Current sensitive Doppler technology allows imaging of flow and direct measurements of Doppler indices in very small vessels [13][14][15]. The intraplacental fetal artery may be a more appropriate site for studying vascular resistance in the fetoplacental vascular tree [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation